Social media and constructing the digital identity of organizations: Bibliometric analysis - Wojciech Czakon; Monika Jedynak; Aneta Kuźniarska; Karolina Mania (Entrepreneurial Business and Economics Review (EBER), 2023)
Objective: The study aimed to map the stock of knowledge on organizational identity in a digital environment. Research Design & Methods: We systematically reviewed the literature to map the current research landscape and identify gaps that need to be addressed to better understand how organizational identity is constructed in a digital environment. We used a bibliometric visual analysis to provide a comprehensive overview of the field. We ran a co-occurrence of words analysis to identify central and peripheral themes. Findings: Organizational identity and digital organizational identity seem to be topics detached from mainstream research. Most of the literature has adopted the individual level of analysis and left other levels of analysis unattended, including the organizational level in particular. We see this gap as a major theoretical and empirical vacuum in the existing literature. Implications & Recommendations: We identified a research gap regarding the lack of research on the construction of organizational identity in the digital environment at various levels of analysis. We also found that scholars did not devote attention to the micro level of analysis, i.e. individual interactions such as posts, tweets, etc. although it may be instrumental to the construction of an organization's digital identity. Contribution & Value Added: The article contributes to research on organizational identity shaped in the digital world, especially from the perspective of social media. We show gaps in existing approaches and levels of analysis.
Keywords: M15; M14; M19; 330; communication; digital communication; digital identity; social media; organizational identity